If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 = 3x + 12 Reorder the terms: -2 + 6x = 3x + 12 Reorder the terms: -2 + 6x = 12 + 3x Solving -2 + 6x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 6x + -3x = 12 + 3x + -3x Combine like terms: 6x + -3x = 3x -2 + 3x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 3x = 12 + 0 -2 + 3x = 12 Add '2' to each side of the equation. -2 + 2 + 3x = 12 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 12 + 2 3x = 12 + 2 Combine like terms: 12 + 2 = 14 3x = 14 Divide each side by '3'. x = 4.666666667 Simplifying x = 4.666666667
| 12x+3=9x+21 | | 2000=150+225*3.50x | | 2000=150+225*3.50 | | 90=15*x-3 | | 90=15(x)-3 | | (-1)*b=0 | | 3.5x-1=0.5(7x+2) | | f(x)81x^2-100=0 | | x=1x^2+13x+40 | | 6(3a-b)-6(5b-7a)= | | (x)=1x^2+5x-50 | | X+.071=3 | | f(x)=1x^2+5x-50 | | x=1x^2-9x+14 | | 5(k+1)=16 | | f(x)=1x^2-9x+14 | | x+.07=3 | | 0.6666667y+6=y | | 3t+8(2t-6)=16-4(v+7) | | 11x-9y=14 | | f(x)=5cosx | | 2(1.5m+3)=8.5m-1 | | 6p+11q+4= | | (13b-5)-3(4b+1)=-4 | | -3(6p+4)-2(4-14p)=3(9+3p) | | 80=4w+5 | | 2x+8=6x+2 | | m+11.3=-7.2 | | -66-5x+x^2=0 | | 2m-4m=6 | | x+31=14 | | 8x-15x-30x-51x=53x+31x-72 |